The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2008
DOI: 10.7870/cjcmh-2008-0020
|View full text |Cite
|
Sign up to set email alerts
|

Findings from A Comparison of Mental Health Services in Primary Care and Outpatient Mental Health Services

Abstract: This project used the Colorado Client Assessment Record to compare individuals being seen by mental health teams in primary care with individuals being seen in outpatient services in the same community and to look at the implications for service delivery. While more individuals with a psychotic illness were seen in outpatient settings, many individuals seen in primary care had similar levels of need to those in outpatient clinics. Family physicians were more actively involved in the care of patients being seen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 16 publications
0
7
0
Order By: Relevance
“… 19 The founder of the shared care model (the Canadian Collaboration Mental Health Initiative) defined shared care as ‘collaborative mental healthcare models of practice in which consumers, their families and caregivers, together with healthcare providers from a variety of primary healthcare and mental health settings—each with different experience, training, knowledge and expertise—work together to provide better coordinated and more effective services for individuals with mental health needs’. 34 These services include mental health promotion, illness prevention, detection and treatment of mental illnesses, rehabilitation and recovery support. Shared care can encompass a broad range of activities, such as regular visits by a mental healthcare worker to a primary healthcare setting and regular telephone consultations between primary healthcare and mental healthcare providers.…”
Section: Methods and Analysismentioning
confidence: 99%
See 1 more Smart Citation
“… 19 The founder of the shared care model (the Canadian Collaboration Mental Health Initiative) defined shared care as ‘collaborative mental healthcare models of practice in which consumers, their families and caregivers, together with healthcare providers from a variety of primary healthcare and mental health settings—each with different experience, training, knowledge and expertise—work together to provide better coordinated and more effective services for individuals with mental health needs’. 34 These services include mental health promotion, illness prevention, detection and treatment of mental illnesses, rehabilitation and recovery support. Shared care can encompass a broad range of activities, such as regular visits by a mental healthcare worker to a primary healthcare setting and regular telephone consultations between primary healthcare and mental healthcare providers.…”
Section: Methods and Analysismentioning
confidence: 99%
“…Shared care is a collaboration between general practice and mental health services and enables a ‘best of both worlds’ scenario with the opportunity to provide high-quality holistic care to support the recovery process of people with mental health difficulties 19. The founder of the shared care model (the Canadian Collaboration Mental Health Initiative) defined shared care as ‘collaborative mental healthcare models of practice in which consumers, their families and caregivers, together with healthcare providers from a variety of primary healthcare and mental health settings—each with different experience, training, knowledge and expertise—work together to provide better coordinated and more effective services for individuals with mental health needs’ 34. These services include mental health promotion, illness prevention, detection and treatment of mental illnesses, rehabilitation and recovery support.…”
Section: Methods and Analysismentioning
confidence: 99%
“…At the same time, a survey of PCPs indicated that the barriers to accessing mental health care for their patients exceed those for other specialty services, for a variety of reasons (Cunningham, 2009). As a result, various governmental agencies are encouraging greater sensitivity to behavioral and mental health issues in the primary care setting (e.g., Kates, Ackerman, Crustolo, & Mach, 2006; Kirkcaldy & Tynes, 2006; Power & Chawla, 2008).…”
Section: Primary Care Psychologymentioning
confidence: 99%
“…In most countries, primary care is the first point of contact in the health‐care system for many individuals with mental health problems 1 . Increasingly, interprofessional primary care teams are optimally positioned to address specific mental health needs of patients along with other physical and/ behavioural needs 2,3 .…”
Section: Introductionmentioning
confidence: 99%
“…In most countries, primary care is the first point of contact in the health-care system for many individuals with mental health problems. 1 Increasingly, interprofessional primary care teams are optimally positioned to address specific mental health needs of patients along with other physical and/ behavioural needs. 2,3 Given the high prevalence of common mental disorders (CMDs)-such as anxiety and depression-in primary care 1 and the challenges of clinical management, there is substantial benefit from the collaboration between health and mental health professionals who can work together as a team.…”
Section: Introductionmentioning
confidence: 99%